Performance evaluation of fiber-reinforced concrete produced with steel fibers extracted from waste tire - Zeybek, Özer; Özkılıç, Yasin Onuralp; Çelik, Ali İhsan and Deifalla, Ahmed Farouk and Ahmad, Mahmood and Sabri Sabri, Mohanad Muayad (Frontiers in Materials, 2022)
With the increasing number of vehicles in the world, the amount of waste tires is increasing day by day. In this case, the disposal of expired tires will cause serious environmental problems. In recent years, instead of disposing of tire wastes, most of them have been started to be recycled to produce fiber-reinforced concrete. Thus, steel fibers recovered from waste tires have been preferred as an alternative to industrial steel fibers due to their environmentally friendly and low-cost advantages. In this study, an experimental study was carried out to explore the effect of fiber content on the fresh and hardened state of the concrete. To achieve this goal, in the fresh case workability of the concrete mixture with three different fiber content (1%, 2%, and 3%) was investigated. The slump test was also conducted on the test samples and slump values of the reinforced concrete with tire-recycled fibers were compared with the plain concrete. After 28 days of curing, mechanical properties such as compressive strength, splitting tensile strength, and flexure strength were explored to observe the performance of the reinforced concrete with tire-recycled steel fibers. According to the test results, tire-recycled steel fiber plays an important role to enhance the performance of the concrete. There is an improvement in the mechanical properties of the concrete with the increase of the volume fraction of the steel fiber. Furthermore, Scanning Electron Microscope (SEM) analysis was performed to observe the interaction between tire-recycled fibers and concrete. Lastly, empirical equations based on fiber content were also proposed to estimate compressive strength and splitting tensile strength in practical applications.